Personality Traits and Mental Health: Considering the Role of Age - Weixi Kang; Antonio Malvaso (Psychology International)
Personality traits are dispositional characteristics that capture basic individual differences. The Big Five model is one of the most studied personality models and can be conceptualized using other personality models as well. Personality traits are also closely associated with mental health, which is our general state of well-being. However, it is largely unknown how the relationships between the Big Five personality traits and mental health may differ with age. By analyzing data using hierarchical regression and multiple regressions, the current research found that age modulates the associations between all Big Five personality traits (i.e., Neuroticism, Agreeableness, Openness, Conscientiousness, and Extraversion) and mental health. These findings can be mostly explained by predominant development theories. The current study indicates the necessity for considering age differences when investigating the relationships between the Big Five personality traits and mental health. Psychologists may want to work out a way to improve mental health based on age and personality characteristics.